Households' resilience and local commercialization in Thailand - Menglan Wang; Manh Hung Do (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2023)
Understanding households' resilience strategies under uncertainties is important in several domains including social protection, adaptation to climate change, minimizing disaster-related risks, and humanitarian aid. At the same time, food security is an important problem for developing countries, especially in places where are vulnerable to external shocks. We use the data of 1648 identical households from Thailand collected in 2010, 2013, and 2016 to examine the factors affecting households' resilience capacities and the impacts of these capacities on household consumption and crop commercialization. We employ savings per capita as households' absorptive capacity and income diversification index as households' adaptive capacity. We take into account household consumption and crop commercialization as the indicators of local food systems. Our results show that the experience of shocks in previous years positively correlates with households' saving per capita and income diversification. Further, a better absorptive capacity in the form of better savings and a better adaptive capacity in the form of higher income diversification have a significant and positive influence on household expenditure per capita and crop commercialization. Therefore, development policies and programs aiming to improve income, increase savings, and provide income diversification opportunities are strongly recommended.
Keywords: C33; Q00; Q12; 330; Absorptive capacity; Adaptive capacity; Crop commercialization; Panel data; Instrumental variable